2019
DOI: 10.1111/irv.12628
|View full text |Cite
|
Sign up to set email alerts
|

Influenza surveillance in Middle East, North, East and South Africa: Report of the 8th MENA Influenza Stakeholders Network

Abstract: The Middle‐East and Africa Influenza Surveillance Network ( MENA ‐ ISN ), established in 2014, includes 15 countries at present. Country representatives presented their influenza surveillance programmes, vaccine coverage and influenza control actions achieved, and provided a list of country surveillance/control objectives for the upcoming 3 years. This report details the current situation of influenza surveillance and action plans to move forward in MEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Our results support the notion that health behaviors differ with each immigrant generation [16]. Influenza vaccination remains uncommon in the MENA region, in part due to low vaccine efficacy, as well as misbeliefs and fear concerning the vaccine [29,30]. Vaccination rates may increase with each Arab American generation due to separation from these health beliefs.…”
Section: Discussionsupporting
confidence: 78%
“…Our results support the notion that health behaviors differ with each immigrant generation [16]. Influenza vaccination remains uncommon in the MENA region, in part due to low vaccine efficacy, as well as misbeliefs and fear concerning the vaccine [29,30]. Vaccination rates may increase with each Arab American generation due to separation from these health beliefs.…”
Section: Discussionsupporting
confidence: 78%
“…The World Health Organization cites reports from developed countries that estimate the total annual cost of influenza infections between U$1 million to U$6 million per 100,000 [ 16 ]. Epidemiological studies on ALRI in general and pediatric influenza are scarce in the Middle East, including Jordan [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This report concluded that influenza poses a significant threat, especially in high-risk groups (children under five, elderly, pregnant women, and immunosuppressed individuals). This finding called for additional funding and planning to address such a threat [ 18 ]. 6-year surveillance on influenza hospitalization with SARS was performed in Jordan by Abdullat et al ., it concluded that influenza was associated with substantial morbidity and mortality in the country; with influenza detected in 9% of SARS cases and had a death rate of 3% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This burden persists despite uptake that exceeds 60% within the targeted groups, and 20% overall. Influenza incidence in the Palestinian territories is unreliably reported but is likely to be even higher given the greater population density, [ 7 ] and the considerably low vaccination coverage [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%